1998
DOI: 10.1161/01.cir.98.21.2227
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Modulation of Acute Myocardial Infarction

Abstract: on behalf of the ECLA (Estudios Cardiológicos Latinoamérica) Collaborative Group* Background-Several trials have been performed in the past using glucose, insulin, and potassium infusion (GIK) for the treatment of acute myocardial infarction (AMI). Because of continuing uncertainty about the potential role of this therapeutic intervention, we conducted a randomized trial to evaluate the impact of a GIK solution during the first hours of AMI. Methods and Results-Four hundred seven patients with suspected AMI ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(52 citation statements)
references
References 26 publications
(15 reference statements)
1
47
0
2
Order By: Relevance
“…To confer its cardioprotection, insulin needs to be given at least during the first 15 min of reperfusion in an isolated rat heart model where it activates PI3K signalling pathways [19][20][21]. Insulin may also reduce mortality as suggested by a retrospective analysis of patients with acute myocardial infarction undergoing reperfusion therapy [9]. Using insulin infusions in the same dosage range as in the isolated heart and cardiomycocyte experiments to protect the ischemic myocardium upon reperfusion would constitute a safe and cheap technique.…”
Section: Possible Clinical Applicationmentioning
confidence: 99%
“…To confer its cardioprotection, insulin needs to be given at least during the first 15 min of reperfusion in an isolated rat heart model where it activates PI3K signalling pathways [19][20][21]. Insulin may also reduce mortality as suggested by a retrospective analysis of patients with acute myocardial infarction undergoing reperfusion therapy [9]. Using insulin infusions in the same dosage range as in the isolated heart and cardiomycocyte experiments to protect the ischemic myocardium upon reperfusion would constitute a safe and cheap technique.…”
Section: Possible Clinical Applicationmentioning
confidence: 99%
“…In the ECLA pilot trial, which assessed the effect of a glucose-insulin-potassium-infusion in patients with acute myocardial infarction, a non-significant reduction in hospital events in patients allocated to glucose-insulin-potassium-infusion and a reduction in mortality in patients additionally treated with reperfusion strategies was observed [152].…”
Section: Secondary Prevention Of Cardiac Dysfunctionmentioning
confidence: 99%
“…G lucose-insulin-potassium (GIK) infusions have been used as metabolic adjuvants in acute myocardial infarction (AMI) [1][2][3][4][5] in an attempt to enhance myocardial glucose uptake and oxidation and take advantage of the efficacy of this substrate in generating ATP. 6,7 Recently, a group of Dutch investigators 8 reported beneficial effects of GIK therapy in patients with AMI treated with percutaneous coronary intervention (PCI).…”
mentioning
confidence: 99%